PENGGUNAAN MEDIA GRAFIS DALAM PROSES PEMBELAJARAN - Safei Safei (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2007)
The existence of teacher in educational sector is very important, because, the teacher is one of components instructional system which decides educational quality in the future. In teaching learning process, a teacher is demanded to do the instruction effec-tively and efficiently. Therefore, the use of graphic media in becomes a solution in teaching learning process with verbal teaching in the classroom. By using graphic media in teaching learning process can increase the learner interest and attention and it can also make clear the material is presented. It is very simple and easy to make it relatively cheaper. Besides that, it can help the teacher in teaching and learning process in order to help the leaner to study.